2021
DOI: 10.1111/ijcp.14219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID‐19 pandemic on anxiety depression and intention to go to hospital in chronic patients

Abstract: Objective: The aim of this study was to investigate the effects of the COVID-19 pandemic on anxiety depression and intention to go to the hospital in chronic patients. Methods:The Bostan Intention to Go to Hospital Scale developed by one researcher (SB) as the data collection tool and the Beck Anxiety-Depression Inventories were used.Results: Of all patients, 56.8% stated that they would go to the hospital in case of emergency and 28.3% expressed that they did not want to go to the hospital even in this case. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…Previous studies have documented the negative effects of the ongoing COVID-19 pandemic on mental health among various groups (Cano et al, 2020 ; Escobar et al, 2020 ; Kaya et al, 2021 ; Ye et al, 2020a ). One particularly vulnerable group is college students, who experienced disruptions to their academic and social life on campus and were forced to move back home (Brooks et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have documented the negative effects of the ongoing COVID-19 pandemic on mental health among various groups (Cano et al, 2020 ; Escobar et al, 2020 ; Kaya et al, 2021 ; Ye et al, 2020a ). One particularly vulnerable group is college students, who experienced disruptions to their academic and social life on campus and were forced to move back home (Brooks et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In one study, anxiety was higher among women, non-medical workers, and pregnant women than among other populations [ 16 ]. In another study, due to anxiety about COVID-19 infection, many participants said that they would not go to the hospital if their disease progressed [ 17 ]. Another study found that depression was higher in individuals with poor health and finances and less social support [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sonbol et al found that PWE who were concerned about the COVID-19 pandemic news and spent 3 h or more following the news had higher depression than the less concerned ones [ 20 ]. Kaya et al reported increased depression levels in PWE if they encountered a COVID-19 patient or had a relative with COVID-19 [ 21 ]. Çilliler and Güven and Stauder et al found that poor sleep quality was associated with higher depressive symptoms in PWE [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%